Potensi Serbuk Daun Pepaya untuk Meningkatkan Efisiensi Pemanfaatan Pakan, Rasio Efisiensi Protein dan Laju Pertumbuhan Relatif pada Budidaya Ikan Nila (Oreochromis niloticus) [Papaya Leaf Powder Potential to Improve Efficiency Utilization of Feed, Protein Efficiency Ratio and Relative Growth Rate in Tilapia (Oreochromis niloticus) Fish Farming] - Gunanti Mahasri; Romziah Sidik; Norma Isnawati (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract  Tilapia is a fish that has high economic value and is an important commodity in the business world of freshwater fish. Some of the things that support the importance of commodities tilapia, among others, have a relatively high resistance to disease, have a wide tolerance to environmental conditions, has the ability to grow well and can thrive well in intensive farming systems. Feeding efficiency can reduce production costs, but still has the required nutritional value of fish is an alternative that should be pursued. Several methods are used to improve feed efficiency, including optimizing digestion and absorption of food and increase the efficiency of the protein with the addition of digestive enzymes. There are two types of digestive enzymes in the enzyme or enzymes endogeneous eksogeneous to help accelerate the process of digestion and hydrolysis. One eksogeneous enzyme is an enzyme papain. The purpose of this study is to analyze the improvement of the efficiency of feed utilization, increasing and enhancing the protein efficiency ratio relative to the growth rate of tilapia due to the addition of papaya leaf powder. The method used is a method laboratory experiments. While the research design used in this research is completely randomized design (CRD), with all the factors conditioning the same and homogeneous, except for the treatment factor. Treatments consisted of 3 treatments and repeated each 6 replications, namely: A1: treatment of feeding with powdered papaya leaves 2%, A2: treatment of feeding with powdered papaya leaves 3%, A3: treatment of feeding with powdered leaves of papaya 4% and C: feeding without addition of the enzyme papain (control). The main parameters in this study is the efficiency of feed utilization, protein efficiency ratio of the feed rate relative pertumhuhan on tilapia, fish protein in meat and fish meat thickness. Fish feed without the addition of the enzyme papain proximate tested. Once given the addition of papaya leaf powder, tested proximate feed back. The amount of feed intake was calculated by weighing the amount of feed that has been consumed during treatment (30 days). The research result analysis showed that papaya leaf powder addition of as much as 2% can improve the efficiency of feed utilization in tilapia fish farming amounted to 36.65%, can increase the protein efficiency ratio amounted to 0.55%, could increase the growth rate relative to the cultivation of tilapia by 2,725% , can increase the protein content in the flesh of tilapia by 17.98%. As for the treatment of papaya leaf powder addition of as much as 3% can increase the thickness of the flesh of tilapia by 38.09%